(untitled) (Boston, 2003)
"Practical English Language Teaching" offers a thorough yet practical overview of language teaching methodology for teachers and teachers in preparation. The principles outlined in each chapter are richly illustrated with vignettes and extracts from real classrooms so the reader can see what the principles "look like" when realized in classroom teaching. The book is divided into three sections: Exploring Skills, Exploring Language, and Supporting the Learning Process. It includes features such as: critical areas of language teaching that are comprehensively addressed with a specific focus on practical techniques, strategies, and tips; world-class specialists like Neil Andersen, Kathleen M. Bailey, Mary Ann Christison, and David Nunan offer a variety of perspectives on language teaching and the learning process; reflection questions invite readers to think about critical issues in language teaching while Action tasks outline strategies for putting new techniques into practice; thoughtful suggestions for books, articles, and Web-sites offer resources for additional, up-to-date information; and, expansive glossary offers short and straightforward definitions of core language teaching terms.
Keywords: English language; Textbooks for foreign speakers